2002
DOI: 10.1105/tpc.003368
|View full text |Cite
|
Sign up to set email alerts
|

The SCFCOI1 Ubiquitin-Ligase Complexes Are Required for Jasmonate Response in Arabidopsis

Abstract: Xie and colleagues previously isolated the Arabidopsis COI1 gene that is required for response to jasmonates (JAs), which regulate root growth, pollen fertility, wound healing, and defense against insects and pathogens. In this study, we demonstrate that COI1 associates physically with AtCUL1, AtRbx1, and either of the Arabidopsis Skp1-like proteins ASK1 or ASK2 to assemble ubiquitin-ligase complexes, which we have designated SCF COI1 . COI1 E22A , a single amino acid substitution in the F-box motif of COI1, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
543
0
7

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 601 publications
(569 citation statements)
references
References 90 publications
19
543
0
7
Order By: Relevance
“…The involvement of ARGOS in auxin signaling is strengthened further by the finding that ARGOS induction by auxin is attenuated in the weak allele axr1-3 and abolished in the strong allele axr1-12; moreover, overexpression of ARGOS partially restores organ growth in axr1-3 ( Figure 6). AXR1 is a component of the ubiquitin-activating enzyme E1 (Leyser et al, 1993), which functions in an early step of auxin signaling (Leyser, 2002) and also may mediate other plant signals, such as jasmonate and light (Schwechheimer et al, 2002;Xu et al, 2002). With respect to ARGOS expression and function, we suspect the existence of as yet unidentified signaling components between AXR1 and ARGOS.…”
Section: Argos Mediates the Auxin Signal To Affect Lateral Organ Devementioning
confidence: 98%
“…The involvement of ARGOS in auxin signaling is strengthened further by the finding that ARGOS induction by auxin is attenuated in the weak allele axr1-3 and abolished in the strong allele axr1-12; moreover, overexpression of ARGOS partially restores organ growth in axr1-3 ( Figure 6). AXR1 is a component of the ubiquitin-activating enzyme E1 (Leyser et al, 1993), which functions in an early step of auxin signaling (Leyser, 2002) and also may mediate other plant signals, such as jasmonate and light (Schwechheimer et al, 2002;Xu et al, 2002). With respect to ARGOS expression and function, we suspect the existence of as yet unidentified signaling components between AXR1 and ARGOS.…”
Section: Argos Mediates the Auxin Signal To Affect Lateral Organ Devementioning
confidence: 98%
“…In the absence of sugar, JA treatment failed to induce the accumulation of anthocyanin and the DFR transcript, indicating that JA synergistically modulates sugar-induced anthocyanin biosynthesis by regulating the expression of the DFR gene (Loreti et al, 2008). The F-box protein Coronatine Insensitive-1 (COI1), which forms the SCF COI1 complex with ASK1/ASK2, Cullin1, and Rbx1, is involved in diverse JA responses (Xu et al, 2002), most of which are disrupted in the Arabidopsis mutant coronatine insensitive 1 (coi1). A coi1-1 mutant with a premature stop codon at W467 failed to accumulate anthocyanin in response to methyl JA (Reymond and Farmer, 1998;Xie et al, 1998).…”
Section: Interaction Of Sugar With Jamentioning
confidence: 99%
“…The JA-ZIM-domain (JAZ) family proteins, which are substrates of the SCF COI1 complex, consist of 12 members and function as negative regulators of JA responses, probably by directly inhibiting various transcriptional regulators (Xie et al, 1998;Xu et al, 2002). Protein-protein interaction studies revealed that JAZs directly interact with bHLHs (TT8, GL3, and EGL3) and R2R3-MYB TFs (PAP1 and GL1) in the MBW complex ( Fig.…”
Section: Interaction Of Sugar With Jamentioning
confidence: 99%
“…The mode-ofaction of NPR1 in the cytosol is unknown. It is tempting to speculate, however, that it interferes with the previously identified SCF COI1 ubiquitin-ligase complex [47,48] that regulates JA-responsive gene expression through targeted ubiquitination and subsequent proteasome-mediated degradation of a putative negative regulator of JA signaling.…”
Section: Systemic Signalingmentioning
confidence: 99%